Post-cardioversion Improvement in LV Function Defined by 4D Flow Patterns and Energetics in Patients With Atrial Fibrillation - Karlsson, Lars Olof; Erixon, Hanna; Ebbers, Tino; Bolger, Ann; Carlhäll, Carl-Johan (Frontiers in Physiology, 2019)
Background Atrial fibrillation (AF) is a prevalent cause of cardiovascular morbidity, including thromboembolism and heart failure. Left ventricular dysfunction (LVD) detected in AF patients may be either precursor or consequence of the arrythmia. Successful cardioversion of chronic AF is often followed by a transient period of left atrial (LA) stunning, where depressed mechanical atrial contraction persists despite reinstitution of sinus rhythm. To determine if AF-associated LVD would improve with resolution of LA dysfunction, AF patients were examined immediately and 4 weeks after cardioversion to sinus rhythm. 4D flow cardiovascular magnetic resonance (CMR) assesses ventricular function according to the volumes and energetics of functional components of the LV volume. Previously described 4D CMR markers of LV dysfunction include decreased volume and end-diastolic kinetic energy (KE) of the Direct flow, which is the portion of LV volume that passes directly from inflow to outflow in a single cycle. We hypothesize that impaired LV flow patterns and energetics will be found immediately after cardioversion during atrial stunning, and that those parameters will improve as atrial function returns. Methods Ten patients with a history of AF underwent CMR 2-3 hours (Time-1) and 4 weeks (Time-2), following electrical cardioversion to sinus rhythm. 4D phase-contrast velocity data and morphological images were acquired at a 3T CMR system. Using a previously evaluated method, pathlines were emitted from the LV end diastolic volume (LVEDV) and traced forward and backward in time until end-systole. The LVEDV was automatically separated into four functional flow components whose volume and KE were calculated. Results Left atrial fractional area change increased over the follow-up period (P=0.001), indicating recovery of LA mechanical function. LVEF increased between Time-1 and Time-2 (P=0.003); LVEDVI did not change (P=0.319). Over that interval, the ratios of Direct flow/LVEDV volume and KE increased (P=0.001 and P=0.003, respectively), while the ratios of Residual volume/LVEDV volume and KE decreased (P=0.001 and P=0.005, respectively). Conclusion Post-cardioversion recovery of LA function was associated with improvements in conventional and 4D CMR markers of LV function. Flow-specific measures demonstrate the negative but potentially reversible impact of LA dysfunction on volume and energetic aspects of LV function.